2021
DOI: 10.3390/math9212789
|View full text |Cite
|
Sign up to set email alerts
|

The k-Metric Dimension of a Unicyclic Graph

Abstract: Given a connected graph G=(V(G),E(G)), a set S⊆V(G) is said to be a k-metric generator for G if any pair of different vertices in V(G) is distinguished by at least k elements of S. A metric generator of minimum cardinality among all k-metric generators is called a k-metric basis and its cardinality is the k-metric dimension of G. We initially present a linear programming problem that describes the problem of finding the k-metric dimension and a k-metric basis of a graph G. Then we conducted a study on the k-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 15 publications
1
43
0
Order By: Relevance
“…then u and w are called twin vertices of G. We begin with the following observations from [16,17,1,9] which we use in our proofs.…”
Section: General Boundsmentioning
confidence: 99%
See 1 more Smart Citation
“…then u and w are called twin vertices of G. We begin with the following observations from [16,17,1,9] which we use in our proofs.…”
Section: General Boundsmentioning
confidence: 99%
“…A subset S ⊆ V (G) is a distance-k resolving set of G if |S ∩ R k {x, y}| ≥ 1 for any pair of distinct vertices x and y in G, and the distance-k dimension of G, denoted by dim k (G), is the minimum cardinality over all distance-k resolving sets of G. The distance-k dimension of graphs was studied in [1], where it was also investigated more generally for metric spaces. The complexity of the problem was studied in [11] and [10], where it was shown that computing dim k (G) is an NP-hard problem for any positive integer k. The graphs G with dim k (G) = 1 were characterized in [9], which also investigated the problem in a more general setting.…”
Section: Introductionmentioning
confidence: 99%
“…Let us recall the following definitions from [7]. A vertex of degree at least three in a graph G will be called a major vertex of G. Any end-vertex (a vertex of degree one) u of G is said to be a terminal vertex of a major vertex v of G if d G (u, v) < d G (u, w) for every other major vertex w of G. The terminal degree ter(v) of a major vertex v is the number of terminal vertices of v. Let M(G) be the set of exterior major vertices of G having terminal degree greater than one.…”
Section: Bounds On Dim(g)mentioning
confidence: 99%
“…There are also several natural extensions of the definition of metric dimension in the literature, some of them, combining it with the idea of domination. See, for example [13,19,20] Another natural extension of metric dimension appears in [7]. See also [8,9,10,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation